Impact of preoperative double-J stent placement on stone recurrence following flexible ureteroscopic lithotripsy - Chao Zuo; Yue Li; Honglei Liu; Zihui Gao; Yaming Gu (Journal of International Medical Research)
Objective This study investigated the effect of preoperative double-J stent placement on stone recurrence following flexible ureteroscopic lithotripsy and analyzed the risk factors for postoperative stone recurrence. The study aimed to provide a clinical reference for better management of the identified risk factors. Methods This retrospective study collected data from patients who underwent flexible ureteroscopic lithotripsy for urinary stones between April 2023 and May 2024. Patients were divided into two groups based on whether a double-J stent was placed preoperatively. Comparisons were made between the stent and nonstent groups. Univariate and multivariate logistic regression analyses were performed to identify the risk factors for postoperative stone recurrence. Results The recurrence rate was 19.51% in the nonstent group and 1.47% in the stent group, with a statistically significant difference (P = 0.001). Stone removal strategy (P < 0.001), preoperative systolic blood pressure (P = 0.017), and intraoperative blood loss (P = 0.044) were identified as risk factors for postoperative recurrence, with stone removal strategy (P = 0.013) and preoperative systolic blood pressure (P = 0.017) being independent risk factors. Conclusions Preoperative placement of a double-J stent is associated with a lower recurrence rate of stones following flexible ureteroscopic lithotripsy than no preoperative stenting. Stone removal strategy and preoperative systolic blood pressure are independent risk factors for stone recurrence following flexible ureteroscopic lithotripsy.